1993
DOI: 10.1002/j.2161-1912.1993.tb00232.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Student Perceptions of Secondary Vocational Education: Implications for Multicultural Career Counseling

Abstract: Comparative analysis of 204 African‐American and White students' perceptions toward secondary vocational education revealed that students formed perceptions toward these programs from a multidimensional perspective. Generally, African‐American female students held positive perceptions whereas African‐American male students held negative perceptions toward vocational education programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…Thus, it is important to be aware of various potential points of view and respect the fact that more than one perspective is legitimate. When working with a client regarding AT, there are several key points to consider: the client's and family's degree of acculturation, their racial-ethnic identity, the views of their own culture and of the dominant culture, and their level of formal education (Rojewski, 1997). LaPlante, Hendershot, and Moss ( 1992) found that economic status was related to ownership of devices, who paid for the devices (self or third-party payer), and unmet need for devices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is important to be aware of various potential points of view and respect the fact that more than one perspective is legitimate. When working with a client regarding AT, there are several key points to consider: the client's and family's degree of acculturation, their racial-ethnic identity, the views of their own culture and of the dominant culture, and their level of formal education (Rojewski, 1997). LaPlante, Hendershot, and Moss ( 1992) found that economic status was related to ownership of devices, who paid for the devices (self or third-party payer), and unmet need for devices.…”
Section: Discussionmentioning
confidence: 99%
“…Barney (1991) emphasized that speaking another language is a major barrier to understanding the client's point of view. Furthermore, the impact of AT on self-image and self-esteem must be considered (Kohn, Enders, Preston, & Motloch, 1983;Rojewski, 1997). Other possible consequences of receiving a device should also be taken into account, such as whether the residence is large enough to accommodate the device and whether other devices or modifications are necessary (and attainable) to facilitate use of the device, such as needing a ramp and a van with a lift to effectively use a power wheelchair or scooter, or widening a doorway to allow entry into the bathroom to use bathing and toileting aids (Kohn et al, 1983).…”
Section: Discussionmentioning
confidence: 99%